Answer:
h'(-1) = 5
Explanation:
Given - The table above gives values of f, f’, g, and g’ at selected values
of x.
x f(x) f'(x) g(x) g'(x)
-1 6 5 3 -2
1 3 -3 -1 2
3 1 -2 2 3
To find - If h(x) = f(g(x)), then h’(1) = ......?
Proof -
Given that,
h(x) = f(g(x))
⇒h'(x) = f'(g(x))
⇒h'(1) = f'(g(1))
Now,
g(1) = -1
⇒f'(-1) = 5
⇒h'(-1) = 5
Answer:
give me brainlist ok? I rly need it
Answer:french
Explanation: bc in the mid 18 centuries the traveled to north america
Answer:
d) Arousal Theory
Explanation:
It is also believed that strong emotions trigger the formation of strong memories, and weaker emotional experiences form weaker memories; this is called arousal theory (Christianson, 1992).
lumen learning dot com